THE DEVELOPMENT OF INDONESIAN ISLAMIC LAW: A Historical Overview (JOURNAL OF INDONESIAN ISLAM, 2015)
Islamic Law is a set of promoted regulations adjusting human relationship to the Creator, human being and the environment based on Islamic doctrines. The Islamic Law has been established in Indonesia and effectively implemented in Indonesian Religious Court based on Law Number 7 of 1989. The law covers the areas of marriage, inheritance, will, bequest, benefaction and alms. In addition, especially in Aceh, with its peculiar feature, Islamic Law has been applied normatively, and in several areas it has been applied based on Local Regulations. However to perform the Islamic Law, it depends on faith and piety of the members of Islam. Thereby, although the formal law in juridical manner of Islamic Law in Indonesia was justly applied in limited civil law, however the Muslim society have stepped forward in applying Islamic Law in various Islamic social institutions.